2006
DOI: 10.1007/s10853-005-5929-1
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the relaxor behavior of sol-gel derived Ba(Zr x Ti1− x )O3 (0.30≤x≤0.70) thin films

Abstract: We have studied the relaxor behavior of sol-gel derived Ba(Zr x Ti 1−x )O 3 (0.30≤ x≤0.70) thin films. The plausible mechanism of the relaxor behavior has been analyzed from the dielectric data and micro-Raman spectra. Substitution of Zr +4 for Ti +4 in BaTiO 3 lattice reduces its long-range polarization order yielding a diffused paraelectric to ferroelectric phase transition. The solid solution system is visualized as a mixture of Ti +4 rich polar region and Zr +4 rich regions and with the increase in Zr cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
39
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(44 citation statements)
references
References 21 publications
5
39
0
Order By: Relevance
“…These observations were in agreement with previous reports, where a similar behavior had been observed for BaZr 0.4 Ti 0.6 O 3 ceramics and thin films. [12,15,27] Similar temperature dependence has also been observed for other compositions as well. The dip at ∼120 cm −1 persisted at temperatures higher than the dielectric constant maximum (at ∼145 K), which suggested that the rhombohedral structure was retained in the whole temperature range studied.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…These observations were in agreement with previous reports, where a similar behavior had been observed for BaZr 0.4 Ti 0.6 O 3 ceramics and thin films. [12,15,27] Similar temperature dependence has also been observed for other compositions as well. The dip at ∼120 cm −1 persisted at temperatures higher than the dielectric constant maximum (at ∼145 K), which suggested that the rhombohedral structure was retained in the whole temperature range studied.…”
Section: Resultssupporting
confidence: 83%
“…The intensity variation in the present case did not show any plateau on cooling below freezing temperature as has been demonstrated for BaZr 0.4 Ti 0.6 O 3 . [12,27] This may be due to the fact that the freezing temperature for BaZr 0.5 Ti 0.5 O 3 is (∼26 K) well below the lowest temperature accessible in the present Raman measurements. [8] As both Zr and Ti have the same valency but differ slightly in their ionic radii, random distribution of Zr ions is not expected to give rise to strong random local electric fields that break longrange polar correlations.…”
Section: Resultsmentioning
confidence: 66%
“…Micro-Raman spectroscopy is a valuable technique to investigate structure property relationship such as coherence length, phonon life time, vibrational state of imperfect material, dynamic behavior of optical modes, crystal symmetry, etc. [15] In this report, temperature-dependent Raman spectroscopic studies were done on lead-free Ba(Ti 0.70 ,Sn 0.30 )O 3 relaxors in order to understand the change in their local structure and symmetry. The sequences of transitions were observed as a function of temperature, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, all the aforementioned questions are addressed by investigating, analysing and comparing with experiments the complex dielectric response of disordered BZT crystal numerically obtained in the THz regime, via a combination of a first-principles-based effective Hamiltonian and a molecular dynamics (MD) technique. BZT is chosen because it is a lead-free relaxor that has already attracted a lot of attention 19,27,38,[44][45][46][47][48] . In relaxors, most experimental works were performed in the kilohertz regime, which is (unfortunately) not accessible by our MD techniques.…”
mentioning
confidence: 99%